Money, Growth, Distribution, and Prices in a Simple Sraffian Economy - Milind Rao (Levy Economics Institute of Bard College, 1992)
Rejecting neoclassical notions of supply and demand, Sraffa demonstrated that relative prices are determined by the profit rate. However, a Sraffa model fails to explicitly describe the determination of output, growth, and accumulation. Rao closes this model with a monetary sector, and examines the effects in both a Sraffian and a Classical world. Rao integrates a two class, simple Sraffian production economy with an assets market. The production side yields capital and consumption goods using Sraffian technology, while assets consist of money (printed and distributed by the Central Bank) and the stock of capital. Different approaches to the labor market yield two distinct models: Sraffian and Classical. The principal conclusion is that, in a Sraffian world, Central Bank policy, via its influence on the profit rate, controls the long-run distribution of income and relative prices. In a Classical regime-in which the real wage (and so the profit rate) is exogenously driven the Central Bank controls long-run economic growth.
Keywords: 330